Upregulated Expression of a Unique Gene by Hepatitis B x Antigen Promotes Hepatocellular Growth and Tumorigenesis - Zhaorui Lian; Jie Liu; Li Li; Xianxing Li; N. Lale Satiroglu Tutan; Marcy Clayton; Meng-Chao Wu; Hong-Yang Wang; Patrick Arbuthnot; Michael Kew; Mark A. Feitelson (Neoplasia: An International Journal for Oncology Research, 2003)
Hepatitis B x antigen (HBxAg) is a trans-activating protein that may be involved in hepatocarcinogenesis, although few natural effectors of HBxAg that participate in this process have been identified. To identify additional effectors, whole cell RNA isolated from HBxAg-positive and HBxAg-negative HepG2 cells were compared by polymerase chain reaction select cDNA subtraction, and one clone, upregulated gene, clone 11 (URG11), was chosen for further characterization. Elevated levels of URG11 mRNA and protein were observed in HBxAg-positive compared to HBxAg-negative HepG2 cells. Costaining was observed in infected liver (P<.01). URG11 stimulated cell growth in culture (P<.01), anchorage-independent growth in soft agar (P<.001), and accelerated tumor formation (P<.01), and yielded larger tumors (P<.02) in SCID mice injected subcutaneously with HepG2 cells. These data suggest that URG11 is a natural effector of HBxAg that may promote the development of hepatocellular carcinoma.